Different effects of working hour reduction on labor-intensive and knowledge-intensive industries in the era of artificial intelligence: a meta-frontier approach. Issue 21 (3rd May 2023) - Kim, Doha; Yeon, Jesun; Kim, Joo Hee; Kim, Minwoo; Song, Yeosol; Lee, Daeho
ABSTRACT: Working hours have been discussed for over 150 years from a variety of perspectives such as worker health, corporate productivity, and job market stability. Despite extensive research in working hour reduction, there is limited evidence on the effect of hours worked by industry characteristics. This study examined the relationship between technical efficiency and working hours. For this, 514 Korean companies were divided into labour-intensive and knowledge-intensive industries, and changes in technical efficiency in each industry were investigated after implementing a working hour reduction policy. The efficiency of the labour-intensive industry improved after a reduction of working hours, whereas that of the knowledge-intensive industry decreased. These results imply that working hours should vary by industry. This study empirically illustrates the effect of reducing working hours and suggests practical guidelines for each country and company to increase technical efficiency by industry.